2013
DOI: 10.1002/cb.1434
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the influence of attachment anxiety and attachment security in consumer formation of attachments to brands

Abstract: This research investigates the formation of consumer attachments to brands contingent upon their attachment anxiety and security. An experiment utilizes a consumer sample and real brands across four product categories (apparel, body care, consumer electronics, and soft drinks) to test the relations between consumer-brand identification and brand attachment dependent on attachment anxiety and attachment security. Consistent with previous research, the findings initially confirm that consumer-brand identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
0
17
0
2
Order By: Relevance
“… Performance anxiety (Banker et al., 2020; Garvey et al., 2016) Anxiety and attachment styles with (Swaminathan et al., 2009; Vlachos et al., 2010; Proksch et al., 2013; Cui, Mrad & Hogg, 2018; Mende et al., 2019) Uncertainty and anxiety towards innovative products (Castaño et al, 2008) …”
Section: Overviewmentioning
confidence: 99%
“… Performance anxiety (Banker et al., 2020; Garvey et al., 2016) Anxiety and attachment styles with (Swaminathan et al., 2009; Vlachos et al., 2010; Proksch et al., 2013; Cui, Mrad & Hogg, 2018; Mende et al., 2019) Uncertainty and anxiety towards innovative products (Castaño et al, 2008) …”
Section: Overviewmentioning
confidence: 99%
“…Prior studies have shown that consumers can form emotional attachments to material possessions (e.g., Kleine and Baker, ), brands (e.g., Park et al, ; Proksch et al, ; Thomson et al, ), celebrities (e.g., Thomson, ), and places (e.g., Debenedetti et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To the best of our knowledge, no prior work in marketing and consumer behaviour has used the prototypical approach to study and measure attachment styles. A literature review that we undertook reveals an ongoing practice of using adapted‐context specific multi‐item scales to measure the anxiety and the avoidance dimensions and then assessing attachment styles by their interaction (see, e.g., Mende and Bolton, ; Mende et al, ; Nguyen and Munch, ; Proksch et al, ). Our two reproaches for this practice are as follows: (i) it is dimension‐centred rather than person‐centred; that is, it focuses on dimensions rather than on persons; and (ii) “by combining attachment dimensions information is lost instead of gained” (Griffin and Bartholomew, :21).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Es por esto que las marcas deben optimizar el uso de sus recursos de tal forma que puedan captar nuestra atención y logren influir con más éxito en nuestra intención de compra. Diversos estudios han demostrado que el apego a la marca influye en la intención de compra (Chavanat, Martinent, & Ferrand, 2009;Esch, Langner, Schmitt, & Geus, 2006;Park, Macinnis, Priester, Eisingerich, & Iacobucci, 2010;Proksch, Orth, & Bethge, 2013), razón por la cual se desea lograr apego emocional por parte de los consumidores hacia las marcas.…”
Section: Introductionunclassified